Avaliação da distribuição das cotas-parte do ICMS devidas aos municípios cearenses: cenários alternativos - Sales, Paulo Sérgio Teixeira (2011)
This study aims to evaluate the change in 2007 on the criteria for transfer of shares in the ICMS to municipalities in Ceará. For both, there will be a comparative analysis between the previous criteria - based on spending - and current - which qualifies through the performance in the sectors education, health and environment, and quantifies the VAF. Thus, the methodology of calculation of indices that are assigned to municipalities brought a breakthrough in terms of fiscal responsibility and control public spending. To assess the effect of these changes on the redistribution of resources, are examined in short-term impacts on economic and social indicators that caused changes in the accounts of municipalities, determining the profile of those that have obtained benefit or loss from it. Quantitative analysis shows that the methodological change has reached the goal of making the transfer more distributive and meritocratic. Since the weighting of the indexes has been created on ad hoc basis, it could be reassessed to allow a weight reduction of Value Added Tax on it to prevent concentration of transfers from the ICMS. To do so, three scenarios are built up for the indexes: i) Concentrating – considers the current official criterion; ii) Less concentrating – simulates a criterion based upon a more distributive transfer; iii) Equitable – simulates a criterion by distributing 50% of the transfer based upon the IVA and the remaining distributed equally among the performance variables. It is concluded that, as long as the weights on the IVA are smaller and greater to the other components, the methodological characteristics of calculating the transfer becomes more meritocratic and less distributive and benefits a larger amount of less developed municipalities.